Respostas
respondido por:
8
2x - y = 1
x + y = 5
2x + x= 5+1
3x=6
x=6/3
x=2
*substitui o valor de x para encontrar o valor de y:
2.2 - y = 1
2 + y = 5
4 - y = 1 .(-1)
2 + y = 5
-4 + y= -1
2 + y= 5
-2+2y=4
2y=4+2
2y=6
y=6/2
y=3
r= {2,3}
x + y = 5
2x + x= 5+1
3x=6
x=6/3
x=2
*substitui o valor de x para encontrar o valor de y:
2.2 - y = 1
2 + y = 5
4 - y = 1 .(-1)
2 + y = 5
-4 + y= -1
2 + y= 5
-2+2y=4
2y=4+2
2y=6
y=6/2
y=3
r= {2,3}
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás